Factors that predict testicular atrophy in patients who underwent inguinal hernia repair - Afandiyev, Faraj; Celasin, Haydar; Culcu, Serdar (International Surgery Journal, 2020)
Background: Some of the patients that undergo inguinal hernia repair develop testicular atrophy. Testicular atrophy development also brings about a lot of problems. In our study, we aimed to determine the rate of development of testicular atrophy and predicting factors in patients that undergo inguinal hernia repair in our hospital. Methods: Patients who underwent inguinal hernia repair in our centre from January 2017 to January 2020 were included in our study. Total number of patients was 158 divided into 2 groups i.e. group-1 (those who developed testicular atrophy after inguinal hernia repair) and group-2 (those who did not develop testicular atrophy after inguinal hernia repair). We investigated the relationship between the development of testicular atrophy and age, hernia type and localization, duration of surgery and anesthesia, perioperative non-steroidal anti-inflammatory drugs (NSAID) and antispasmolytic use, diabetes mellitus and rheumatological disease and, perioperative fluid replacement. Results: Testicular atrophy developed in 6 of the patients (3.79%). We found that testicular atrophy was mostly secondary and mostly visible in cases underwent open repair (p=0.0001); and in which left and bilateral inguinal hernia repair was performed (p=0.014); and in cases with DM and rheumatological diseases (p=0.0001). We also found that the use of perioperative antispasmolytic and NSAID was lower in patients with testicular atrophy (p=0.0001). Conclusions: According to the results of our study, advanced age, secondary and open repair, diabetes mellitus, rheumatological disease history, not using antispasmolytic and NSAID increases the risk of testicular atrophy.